2013
DOI: 10.1016/j.otsr.2013.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive fixation of type B and C interprosthetic femoral fractures

Abstract: Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 24 publications
0
18
0
2
Order By: Relevance
“…Soenen et al reported one of 14 patients dying within six months of the fracture event [12]. Platzer et al reported one of 23 patients dying from cardiac arrest 15 days postoperatively [13], and Ehlinger et al reported one death out of eight patients four months after operation [19]. This study reports three of 15 patients dying within six months postoperatively, including one patient already full weight bearing.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Soenen et al reported one of 14 patients dying within six months of the fracture event [12]. Platzer et al reported one of 23 patients dying from cardiac arrest 15 days postoperatively [13], and Ehlinger et al reported one death out of eight patients four months after operation [19]. This study reports three of 15 patients dying within six months postoperatively, including one patient already full weight bearing.…”
Section: Discussionmentioning
confidence: 68%
“…This studies' conflicting result of incidence of fracture location suggests limited value predicting interprosthetic fracture location with such a small sample size. Ehlinger et al had eight patients treated with locked plates spanning the femur, with healing in an average of 14 weeks [19]. In contrast, Hou et al treated 13 patients with interprosthetic fracture as if they were isolated periprosthetic fractures [10]: four were treated with total joint revision and nine with locking plate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In case of persisting instability, they proposed the placement of an additional anterior plate. Beside periprosthetic and interprosthetic fracture fixation, the orthogonal plating technique was successfully applied in nonunion treatment . Especially in revision surgery, where bone healing might be decelerated or bone defects bridged with bonegrafts, orthogonal plating can provide a stable mechanical environment…”
Section: Discussionmentioning
confidence: 99%
“…Beside periprosthetic and interprosthetic fracture fixation, the orthogonal plating technique was successfully applied in nonunion treatment. 9,21,22 Especially in revision surgery, where bone healing might be decelerated or bone defects bridged with bonegrafts, 23 orthogonal plating can provide a stable mechanical environment. 22 This study has several limitations: Due to the in vitro character of the study, the reinforcing effect of bone healing on the construct stability could not be investigated so that these data focus on direct postoperative primary stability.…”
Section: Discussionmentioning
confidence: 99%